Photoelectrochemical bioanalysis of microRNA on yolk-in-shell Au@CdS based on the catalytic hairpin assembly-mediated CRISPR-Cas12a system. Issue 54 (16th June 2022) - Zeng, Ruijin; Xu, Jianhui; Lu, Liling; Lin, Qianyun; Huang, Xue; Huang, Lingting; Li, Meijin; Tang, Dianping
Abstract : An innovative photoelectrochemical biosensor was designed for the quantitative monitoring of microRNA with horseradish peroxidase-single stranded DNA-encoded magnetic beads cleaved by the catalytic hairpin assembly-mediated CRISPR-Cas12a system by using yolk-in-shell Au@CdS as a photoactive material. Abstract : This work reports on the proof-of-concept of a photoelectrochemical (PEC) biosensor with a horseradish peroxidase-single stranded DNA-encoded magnetic bead (MB-ssDNA-HRP) signal probe cleaved by the catalytic hairpin assembly (CHA)-mediated clustered regularly interspaced short palindromic repeats (CRISPR)-Cas12a system for the quantification of microRNA (miR-21) by using yolk-in-shell Au@CdS as a photoactive material.